Proposal of an Operations Strategy Formulation in PT ABC - Djunaedi, Arie Rachmadi; Yudoko, Gatot (The Indonesian Journal of Business Administration, 2013)
ABC is a heavy-duty equipment and support equipment assembler, provides chrome plating and engineering solution. Problems in the development of the company is how to increase the production in each production line. Constraints incurred in the company due to non optimal operation performance system. This is an obstacle for the company to expand its business. That problem causes difficulties for the company in determining the long-term strategic plan. Evolving business issues will be discussed through strategic audit that is expected could achieve strategic fit. The discussion includes the current situation of the company, corporate governance, external environment, internal environment, and strategic analysis. Constraints on the performance of the operation will be solved by formulating operations strategy. Ability to carry out operations management requires performance measurement. Measurement in meeting customer needs includes productivity, efficiency, effectiveness, and health and safety workplace. Measurement is fundamental to know the capabilities. Thus the company will know the capacity and productivity of the plant. The ability to recognize this capacity will be a fundamental consideration of the company in making a development strategy decision to achieve long-term targets. Changes will occur in the basic performance records, knowledge of the exact production capacity, also in opportunities to make working methods improvement and an appropriate investment. By knowing the production capacity accurately, the coordination of each division in achieving target will be synergic. Holistic measurement of corporate performance can be started by this basic measurement. Key Words: operation strategy, capacity, productivity, measurement